COMPUTER ASSISTED LANGUAGE LEARNING (CALL): Konsep Pembelajaran Bahasa Inggris Berbantuan Komputer - Risma Amin (LP2M Universitas Ibrahimy, 2016)
The world has entered the era of globalization, where the role of language especially English and the role of technology especially Instructional Computer Technology (ICT) are very dominant. These two elements are evolving so intense and must be consumed in all areas of modern education. So required proper interaction system to unify the two components, which is the actualization of language and the computer sophistication. In this case the most suitable and comprehensive approach is Computer Assisted Language Learning (CALL) as a systemic interaction in teaching English process